Fibras elásticas da parede abdominal anterior em pacientes com hérnia ventral - Fachinelli, Aldo (2010)
In the present study samples were collected from abdominal linea alba aponeurosis of 30 patients (15 males and 15 females) aged from twenty to sixty years [30-59], (Mean=44.9±SD=7.3), with hernia of the anterior abdominal wall to evaluate the immunohistochemistry expression and morphometry of the elastic fibers. Nine of the patients were submitted to surgery at the Hospital de Clínicas in Porto Alegre (HCPA), ten of then at the Santa Casa de Misericórdia do Rio de Janeiro (SCMRJ), seven of them at the author’s private clinic (CA) in Caxias do Sul, and four of them at the Hospital Pompeia (HP) in Caxias do Sul. All patients had a hernia of the anterior abdominal wall. Fourteen of these cases were umbilical hernias, ten epigastric hernias and six incisional hernias. Specimens were collected from the midline three centimeters above the umbilical scar and from two centimeters below it. At the laboratory, the specimens were subdivided in two parts. One of these specimens was stained with orcein and the elastic fibers were counted by digital analysis using the applicative Image Pro Plus (Media Cybernetics, Silver Spring, USA). The other specimen was submitted to evaluation through immunohistochemistry analysis utilizing monoclonal anti-Emilin Antibody to EMILIN1 GP115 Elastin microfibril interface located protein TNF (Proteintech Group), in 1:100 dilution. Findings obtained from these patients were compared to findings obtained in a control group of non formolized cadavers from the Medical Examiner’s Office of Caxias do Sul. In this cadaver control group without hernias, aged from twenty to sixty years [20-59] (Mean= 40.5±SD=11.8), the same studies were carried out as in the surgical group with hernias to evaluate the differences in quantity and morphometry of elastic fibers between the two groups. Results show that the total amount of elastic fibers was 35% higher in patients with hernia of the anterior wall of the abdomen than in the cadaver control group with no hernias (p<.05).